2013
DOI: 10.1097/mcg.0b013e31828f531c
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen Genetics and Clinical Features of Self-treated Patients on a Gluten-free Diet

Abstract: Background and Aims Increasingly, persons start a gluten-free diet (GFD) without a clear celiac disease (CD) diagnosis. Human leukocyte antigen (HLA) genotyping is useful in ruling out CD in patients with equivocal results of serologic testing or small-bowel biopsy (SBB), but its utility and the clinical features of patients on self-treated GFD (ST-GFD) are largely unknown. Methods Retrospective study of single tertiary care center cohort compared 137 patients on ST-GFD and 443 patients with well-defined CD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…With data showing that patients with IBS-D may benefit from gluten free diet (GFD), GFD is used with increasing frequency in IBS-D patients [4][5][6]. Although there is little harm beyond cost to a patient on a balanced GFD,CD may be overlooked and complications ignored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With data showing that patients with IBS-D may benefit from gluten free diet (GFD), GFD is used with increasing frequency in IBS-D patients [4][5][6]. Although there is little harm beyond cost to a patient on a balanced GFD,CD may be overlooked and complications ignored.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence to suggest that the prevalence of CD is higher among patients with IBS than in controls [2].Pooled odds ratios (95% confidence intervals) for positive endomysial antibodies and biopsy-proved coeliac disease in cases meeting diagnostic criteria for IBS compared with controls without IBS . Based on this evidence and decision analytic modeling data that suggest cost effectiveness, the Task Force recommends routine serologic screening for coeliac sprue in patients with IBS-D or IBS-M but in resourse constrained countries like India it is not cost effective to screen all IBS-D patients for CD [6]. In our study multivariate analysis showed that out of all variables duration of symptoms more than 6 months, IDA, Hb less than10mg/dl , bone pains and ALT more than 40 mu/ml are the most important predictors of CD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,43,[82][83][84][85] This variation inevitably leads to some of the studies mentioned earlier open to interpretation as to whether patients with NCGS or coeliac disease are being described. Indeed, at a meeting held in 2014 among experts in the field of gluten-related disorders, the panel regularly raised the issue that future studies and identification of biomarkers in NCGS need to be performed in individuals who are HLA-DQ2 and HLA-DQ8 negative so that potential ambiguity with coeliac disease can be avoided.…”
Section: Uncertainties and Future Directionsmentioning
confidence: 99%
“…There are no specific tests for the condition, although a basophil activation test has been suggested to be of use [81]. A large retrospective study found that the condition does not have the HLA associations of coeliac disease [85]. Data on mucosal immunopathology show conflicting results [83,84].…”
Section: Noncoeliac Gluten Sensitivitymentioning
confidence: 99%